HUBUNGAN KONSUMSI KOPI DAN SCREEN-TIME DENGAN LAMA TIDUR DAN STATUS GIZI PADA DEWASA - Kadita, Febiandra; Wijayanti, Hartanti Sandi (Journal of Nutrition College, 2017)
Background: Nutritional problem such as underweight or obesity in adolescents is an important issue that can lead into some disease.1 BMI can be affected with some factor, there were coffee consumption, screen-time and sleep duration. Sleep duration can be affected by coffee consumption and screen-time.Objective: Knowing the relationship of coffee consumption and screen-time with sleep duration and BMI among Adult.Method: A cross-sectional study was conducted on 52 adult in Semarang CafÃ©. We measured weight and height as BMI (kg/m2). Subject interviewed about coffee consumption, screen-time, sleep duration and physical activity. Bivariate analysis used Pearson test and Rank-Spearman test. Multivariate analysis used Multivariate Linear Regression analysis of Backward.Result: Bivariate analysis showed there was a significance relationship between coffee volume and night screen-time with sleep duration (r=-0,3,p=0,03 and r=-0,3,p=0,01). There was a significance relationship between 1 day screen-time and physical activity with BMI (r=0,2, p=0,04 and r=-0,27, p=0,04). Multivariate analysis showed there was a significance relationship between physical activity with BMI (Î²=-0,26, p=0,05).Conclusion: The volume of coffee consumption and screen-time was the factor that caused sleep deprivation. Physical activity was the factor of increased nutritional status.